2012
DOI: 10.1371/journal.pone.0042544
|View full text |Cite
|
Sign up to set email alerts
|

Not All Mice Are Equal: Welfare Implications of Behavioural Habituation Profiles in Four 129 Mouse Substrains

Abstract: Safeguarding the welfare of animals is an important aim when defining housing and management standards in animal based, experimental research. While such standards are usually defined per animal species, it is known that considerable differences between laboratory mouse strains exist, for example with regard to their emotional traits. Following earlier experiments, in which we found that 129P3 mice show a lack of habituation of anxiety related behaviour after repeated exposure to an initially novel environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…Of course, other studies clearly show that mouse substrains differ for several features other than physical activity as a behavior. For instance, it has been shown that the genetic background of the four different mouse substrains affects their vulnerability to cope with environmental challenges, such as exposure to novelty; the authors consistently suggest considering substrain-specific guidelines and protocols, taking the substrain-specific adaptive capabilities into account [31]. We totally agree with the authors of this study.…”
Section: Discussionsupporting
confidence: 80%
“…Of course, other studies clearly show that mouse substrains differ for several features other than physical activity as a behavior. For instance, it has been shown that the genetic background of the four different mouse substrains affects their vulnerability to cope with environmental challenges, such as exposure to novelty; the authors consistently suggest considering substrain-specific guidelines and protocols, taking the substrain-specific adaptive capabilities into account [31]. We totally agree with the authors of this study.…”
Section: Discussionsupporting
confidence: 80%
“…The phenotypic differences between the genetically close sub-strains of the C57BL/6 mice, coupled with the effect of vendor highlight the possible problems associated with choosing the background for genetically modified mice, interpretation of the results and reproducibility of the findings. Obviously, these cautions are not limited only to the C57BL/6 mice [91][92][93] . Moreover, further confounds can be caused by the local breeding schemes at the research institutions 94 .…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of behaviors can be measured, such as avoidance behavior, risk assessment, arousal, exploration, locomotor activity, habituation, social affinity and cognition 2,[8][9][10] . Additionally, the mHB can be combined with a food intake inhibition test, as well as novel object recognition test .…”
Section: Introductionmentioning
confidence: 99%